Bentuk dan Makna Simbolik Ragam Hias pada Masjid Sunan Giri - Rizal Wahyu Bagas Pradana (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2020)
Sunan Giri Mosque is one of the ancient Javanese mosques which was built in the time of Walisongo. Sunan Giri Mosque building has its own uniqueness in its ornament. This uniqueness is rarely found in other mosques in general. This study aims to describe the various ornaments and symbolic meanings found in the Sunan Giri Mosque. This research uses descriptive qualitative research methods. Research data obtained through observation, interviews, documentation, and literature study. Data analysis with data reduction, data presentation, and concluding. Meanwhile, to obtain data validity, using data triangulation and review informants. The results showed the ornament at the Sunan Giri Mosque was influenced by Javanese, Hindu, and Islamic culture. The decoration in the Sunan Giri Mosque takes pre-Islamic elements and is processed, adjusted to the rules contained in the Islamic religion. The ornament in the Sunan Giri Mosque can be grouped into several motives: lung-lungan, patran, padma, tlacapan, saton, kebenan, garuda, praba and surya majapahit motifs. Aside from its role as building decoration, ornament in the Sunan Giri Mosque has symbolic meaning in it. The symbolic meaning is addressed to the Muslims who worship in the mosque. This symbolic meaning contains symbols about noble teachings in Islam, and hopes to Allah SWT. Keywords: architecture; ornament; symbolic meaning; Sunan Giri Mosque Abstrak Masjid Sunan Giri merupakan salah satu masjid kuno Jawa yang dibangun pada zaman walisongo. Bangunan Masjid Sunan Giri memiliki keunikan tersendiri pada ragam hiasnya. Keunikan tersebut jarang ditemui pada masjid-masjid lain pada umumnya. Penelitian ini bertujuan untuk mendeskripsikan ragam hias dan makna simboliknya yang terdapat di Masjid Sunan Giri. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Data penelitian diperoleh melalui observasi, wawancara, dokumentasi, dan studi pustaka. Analisis data dengan reduksi data, penyajian data, dan penarikan kesimpulan. Sedangkan untuk mendapatkan kevalidan data, menggunakan triangulasi data dan informan review. Hasil penelitian menunjukkan ragam hias di Masjid Sunan Giri dipengaruhi oleh budaya Jawa, Hindu, dan Islam. Ragam hias di Masjid Sunan Giri menggambil unsur-unsur pra Islam dan diolah, disesuaikan dengan aturan-aturan yang terdapat dalam agama Islam. Ragam hias di Masjid Sunan Giri dapat dikelompokkan menjadi beberapa motif: motif lung-lungan, patran, padma, tlacapan, saton, kebenan, garuda, praba dan surya majapahit. Selain berperan sebagai penghias bangunan, ragam hias di Masjid Sunan Giri memiliki makna simbolik di dalamnya. Makna simbolik tersebut ditujukkan kepada kaum muslimin yang beribadah di dalam masjid. Makna simbolik ini berisi simbol tentang ajaran-ajaran luhur dalam agama Islam, dan harapan-harapan kepada Allah SWT. Kata kunci: arsitektur; ragam hias; makna simbolik; Masjid Sunan Giri